NleB, a bacterial effector with glycosyltransferase activity targets GADPH function to inhibit NF-κB activation - Gao, Xiaofei; Wang, Xiaogang; Pham, Thanh H.; Feuerbacher, Leigh Ann; Lubos, Marie-Luise; Huang, Minzhao; Olsen, Rachel; Mushegian, Arcady; Slawson, Chad; Hardwidge, Philip R. (My University, 2013)
Modulation of NF-κB-dependent responses is critical to the success of attaching/effacing (A/E) human pathogenic E. coli (EPEC and EHEC) and the natural mouse pathogen Citrobacter rodentium. NleB, a highly conserved type III secretion system effector of A/E pathogens, suppresses NF-κB activation, but the underlying mechanisms are unknown. We identified the mammalian glycolysis enzyme glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as an NleB interacting protein. Further, we discovered that GAPDH interacts with the TNF receptor associated factor 2 (TRAF2), a protein required for TNF-α-mediated NF-κB activation, and regulates TRAF2 polyubiquitination. During infection, NleB functions as a translocated N-acetyl-D-glucosamine (O-GlcNAc) transferase that modifies GAPDH. NleB-mediated GAPDH O-GlcNAcylation disrupts the TRAF2-GAPDH interaction to suppress TRAF2 polyubiquitination and NF-κB activation. Eliminating NleB OGlcNAcylation activity attenuates C. rodentium colonization of mice. These data identify GAPDH as a TRAF2 signaling cofactor and reveal a virulence strategy employed by A/E pathogens to inhibit NF-κB dependent host innate immune responses.
Keywords: NF-κB; NleB; Glycosyltransferase; GAPDH